2016
DOI: 10.1002/ca.22731
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging atlas of the cervical spine musculature

Abstract: The anatomy of the cervical spine musculature visible on magnetic resonance (MR) images is poorly described in the literature. However, the correct identification of individual muscles is clinically important because certain conditions of the cervical spine, for example whiplash associated disorders, idiopathic neck pain, cervical nerve root avulsion and cervical spondylotic myelopathy, are associated with different morphological changes in specific muscles visible on MR images. Knowledge of the precise struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A foundational edict for defining lumbar paravertebral ROI’s from MRI studies has previously been published [ 42 ]. Here, we expand the previous methods [ 57 ] for the cervical pre- and para-vertebral muscles using a number of MRI and E12 sheet plastinate illustrations of vertebral morphology with the aim of standardising muscle ROI definitions. The E12 plastinates provide a unique opportunity to detail specific tissues that may be MR invisible, [ 65 ] leading to natural disagreement across studies where fat-water separation is a target.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A foundational edict for defining lumbar paravertebral ROI’s from MRI studies has previously been published [ 42 ]. Here, we expand the previous methods [ 57 ] for the cervical pre- and para-vertebral muscles using a number of MRI and E12 sheet plastinate illustrations of vertebral morphology with the aim of standardising muscle ROI definitions. The E12 plastinates provide a unique opportunity to detail specific tissues that may be MR invisible, [ 65 ] leading to natural disagreement across studies where fat-water separation is a target.…”
Section: Discussionmentioning
confidence: 99%
“…Fat (F)-Water (W) Fat Infiltration % MFI = (fat signal)/(fat signal + water signal) *100 Elliott et al, 2014 [ 8 ] From Elliott et al, 2007 [ 47 ] for CSA Intra- rater (0.84–0.99) Inter-rater (0.89–0.96) T1 Axial images aligned parallel to C2–3 IVD; measurements from single slice crossing IVDs C2-C3 and C5-C6 MF SSCerv SSCap SpCap LCap/LCol SCM Manual Quantitative Pixel Intensity Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 CSA Elliott et al, 2015 [ 3 ] Not reported Dixon Measurements from single slice per vertebral level C3-C7; alignment and slice selection not reported MF Manual Fat-Water Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 Abbott et al, 2015 [ 6 ] Intra-rater (0.98) Inter-rater (0.93) Dixon Measurements averaged over 5 slices for each vertebral level C3-C7; Slab alignment not reported. MF + SSCerv (combined) Manual with automatic quartile measure Fat-Water Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 Karlsson et al, 2016 [ 5 ] For muscle fat Intra-rater (0.81–0.93) Inter-rater (0.82–0.97) Dixon Axial images aligned parallel to vertebral segments; measurements averaged over 5 slices for each vertebral level C4-C7 MF Manual Fat-Water Fat Infiltration %MFI = (fat signal)/(fat signal + water signal)*100 CSA Au et al, 2016 [ 57 ] Not reported T1 Axial images aligned parallel to C2–3 intervertebral disc; 3D reconstruction IC, IS, LS, LoCap, LoC, LCap, LCol, MF, LoCap, LoCerv, SSCap, SSCerv, SCM, UT Manual N/A N/A Fortin et al, 2017 [ 27 ] Fortin et al, 2018 [ 81 ] From [ 81 ]:Intra-rater (0.83–0.99) Inter-rater (0.38–0.98) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies aimed at tracing these cutaneous pathways when a C1 dorsal ganglion or root does not exist will add to our knowledge of this spinal nerves’ frequent connections to the accessory nerve [ 7 , 8 ]. Additionally, with improved imaging of the neck muscles, newer technologies might better illustrate the nerves of this area [ 9 ]. Although Bergman et al [ 10 ] have mentioned that this nerve “occasionally supplies a cutaneous branch to the back of the head,” further anatomical studies are needed to quantitate this variation and help precisely localize the skin innervated by the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, improved imaging modalities and embryological knowledge will hopefully, in the future, better elucidate the function of such muscle variations of the back [ 9 - 13 ].…”
Section: Discussionmentioning
confidence: 99%